Endoscopic Achilles tendon shortening. (June 2018) - Lui, T.H.
Highlights: Healing in continuity with lengthening of the Achilles tendon is a disabling complication after Achilles tendon rupture. The elongated tendon may have to be shortened to re-establish the length and physiologic tension in triceps surae muscle. Endoscopic Achilles tendon shortening can effectively re-establish the tendon in triceps surae. Abstract: Healing in continuity with lengthening of the Achilles tendon is a disabling complication after Achilles tendon rupture. This results in weakness of ankle plantarflexion and a non-propulsive gait on the affected side. The elongated tendon may have to be shortened or reconstructed to re-establish the length and the physiologic tension in triceps surae muscle and allow restoration of push off. This technical note describes the details of endoscopic shortening of the Achilles tendon.